Gender and Language in Benteng Panynyua English Club - Masita Masita; Rabiatul Adawiah; Devi Triani (Sekolah Tinggi Agama Islam Negeri Majene, 2022)
Men and women are created with much different, especially using language in communication. They have different features in using language although they use same language. It is influenced by differences in gender, characteristic, and thought. In reality many people still do not understand that man and woman have differences in speech. This motivates researchers to find out how the language used differently between man and woman. This research used qualitative design as methodology. This study was conducted in BPEC (Banteng Pannyua English Club), located in Rotterdam fort, South Sulawesi. The participants involved 8 women and 8 men with an intermediate level of English. This study also collected by using Lakoff’s theories related to linguistics features of language based on the gender issue. The researcher found 50 data from the analysis. The result of this study showed man and women have six different types of speech feature in communication. They are Tag Question, Rising Intonation, Lexical Hedge, Intensifier, Emphatic Stress, and Super Polite Form. From this data it can be concluded that man and women have different features in using language.